The impact of mining companies on community development in the Dilokong and Ga-Pila villages in the Sekhukhune and Waterberg Districts of Limpopo Province - Mathabatha, Margaret (University of Limpopo (Turfloop Campus), 2011)
The impact of mining companies on community development in the Dilokong and Ga Pila villages in the Sekhukhune and Waterburg Districts of Limpopo Province has been demonstrated in many ways in this study. The mines have influenced the economic, environmental and social aspects of the Province. The study has revealed that even though mining has placed the Province on the global economic map, the reality is that often the environmental damage is hidden; this was shown by the fact that respondents reported over usage of water by mines. It is clear that the impacts both good and bad of mining begin before mines were even established and does not disappear with the closure of a mine. Mining does not have a good record of contributing to sustainable development or poverty reduction. This research has indicated that mineral extraction is neither necessary nor sufficient for sustained economic growth, and that it has not helped developing communities escape from poverty. This belief is due to the fact that the mines are not following mining charter and other related acts. In conclusion, these benefits may look good on paper, but it is difficult to gauge whether the community are really gaining from this mining projects
Thesis (M.Dev.) --University of Limpopo, 2011
Keywords: Mining companies; Community development; 622.968; Mineral industries; Rural development -- South Africa